2017
DOI: 10.3389/fpls.2017.01770
|View full text |Cite
|
Sign up to set email alerts
|

Viral Diagnostics in Plants Using Next Generation Sequencing: Computational Analysis in Practice

Abstract: Viruses cause significant yield and quality losses in a wide variety of cultivated crops. Hence, the detection and identification of viruses is a crucial facet of successful crop production and of great significance in terms of world food security. Whilst the adoption of molecular techniques such as RT-PCR has increased the speed and accuracy of viral diagnostics, such techniques only allow the detection of known viruses, i.e., each test is specific to one or a small number of related viruses. Therefore, unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…On the contrary, Ion Torrent utilizes the pH variation sequencing method [18,24], whereas the modern platforms, such as Illumina MiSeq and Gene Reader System, utilize the fluorescence emission sequencing method [24,25]. NGS technologies have impressively accelerated research and are becoming employed routinely to seek solutions in different areas of research, as well as provide insights into pathogenicity and virulence of various plant pathogens [26][27][28][29][30][31][32][33][34]. Although NGS is more affordable than first-generation sequencing (considering time and money), it is still not within the reach of many laboratories in undeveloped countries [16].…”
Section: Next-generation Sequencing Its Relevance In Studying Plant mentioning
confidence: 99%
“…On the contrary, Ion Torrent utilizes the pH variation sequencing method [18,24], whereas the modern platforms, such as Illumina MiSeq and Gene Reader System, utilize the fluorescence emission sequencing method [24,25]. NGS technologies have impressively accelerated research and are becoming employed routinely to seek solutions in different areas of research, as well as provide insights into pathogenicity and virulence of various plant pathogens [26][27][28][29][30][31][32][33][34]. Although NGS is more affordable than first-generation sequencing (considering time and money), it is still not within the reach of many laboratories in undeveloped countries [16].…”
Section: Next-generation Sequencing Its Relevance In Studying Plant mentioning
confidence: 99%
“…Next-generation sequencing, known also as massively parallel sequencing or deep sequencing, is a powerful technology that allows the generation of massive amounts of sequence data. There are various approaches or NGS platforms, each with different characteristics and with the potential in some cases to generate as many as three billion reads per run with read lengths that vary from approximately 35 to 800 nucleotides depending on the platform ( Barzon et al, 2011 ; Buermans and den Dunnen, 2014 ; Wu et al, 2015 ; Jones et al, 2017 ; Rott et al, 2017 ). The technology has been proposed as a valuable tool for diagnostic virology ( Adams et al, 2009 ; Barzon et al, 2011 ).…”
Section: Multiplexing Potential Of Next-generation Sequencingmentioning
confidence: 99%
“…The broad-spectrum and unbiased nature of the technology makes it a valuable tool for plant-based metagenomics, allowing the simultaneous screening and detection of populations of graft transmissible agents that include viruses (RNA and DNA), viroids, and phytoplasma in a sample ( Adams et al, 2009 ; Kreuze et al, 2009 ). Jones et al (2017) indicated that the multiplexing potential of NGS (RNA-seq) might allow a researcher to answer the question of how many different viruses are present in a crop plant. NGS even has the power to detect plant viruses that were not detected using current and standard tools that were based on biological, serological, and molecular tests ( Villamor et al, 2016 ).…”
Section: Multiplexing Potential Of Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of next-generation sequencing (NGS) technologies, NGS-based approaches enable us to facilitate the identification of viruses, virus diagnostics, and the assembly of virus genomes [17][18][19][20] . For instance, the NGS technique is widely applied in the study of viruses infecting sweet potato by RNA-Sequencing (RNA-Seq) 17,21 and small RNA-Seq 22,23 .…”
mentioning
confidence: 99%